Evidence of Anaplasma phagocytophilum infection in an island population of Scandinavian moose (Alces alces) in the South-eastern Sweden - Sannö, Axel (SLU/Dept. of Clinical Sciences (until 231231), 2009)
In the second half of the 1990's the moose population on the island Öland declined drastically and the hunters decided to completely stop hunting for moose for a number of years. When the hunting commenced the hunters found the slaughter weights to be lower than expected and the number of calves were also low. The hunters then contacted the Swedish National Veterinary Institute who then initiated a project which this report is a part of. Samples from a total of 40 moose was collected, 32 out of 33 sampled moose were positive for antibodies against Anaplasma phagocytophilum and 4 out of 36 samples were positive by PCR for Ananplasma phagocytophilum. Out of these three were calves and one was a female yearling. Reported slaughter weights for calves were low and the number of observed calves per adult female were half compared to the mainland. This survey indicates that infection with Anaplasma phagocytophilum constitutes a contributing cause for the low number of observed calves in the moose population on the island of Öland. Under senare delen av 90-talet minskade älgstammen på Öland drastiskt och jägarna valde då gemensamt att helt avstå jakt under ett antal år. När jakten återupptogs upplevde jägarna att kalvarna var få till antalet och hade låga slaktvikter. De kontaktade då SVA som inledde ett projekt med omfattande provtagning. Detta arbete är en del av detta projekt. Prover från totalt 40 älgar samlades in, 32 av 33 provtagna älgar visade på antikroppar mot Anaplasma phagocytophilum medan 4 av 36 provtagna var PCRpositiva för Anaplasma phagocytophilum. Av dessa var tre kalvar och en var en kviga. De slaktvikter som rapporterades in för kalv visade på låga siffror och antalet observerade kalvar per vuxet hondjur var hälften av vad som observerats på fastlandet. Denna undersökning pekar på att infektion med kan vara en bidragande orsak till det låga antalet observerade kalvar hos älgpopulationen på Öland.